Slow gait as a motor marker of mild cognitive impairment? the relationships between functional mobility and mild cognitive impairment. Issue 4 (4th July 2019) - Rajtar-Zembaty, Anna; Sałakowski, Andrzej; Rajtar-Zembaty, Jakub; Starowicz-Filip, Anna; Skalska, Anna
ABSTRACT: The purpose of this study was to evaluate the association between functional mobility and mild cognitive impairment in older adults. A total of 800 older adults were recruited (653 controls and 147 subjects with MCI [88 subjects with aMCI and 59 subjects with naMCI]). Motor performance was measured with the Timed Up and Go test (TUG). The demographic factors associated with MCI were: age (OR = 1.05; 95% CI: 1.01–1.09) and the level of education (OR = 0.73; 95% CI: 0.68–0.79). An independent clinical factor associated with MCI was the TUG (OR = 1.14; 95% CI: 1.03–1.27). In the aMCI group, the relation between the TUG and cognitive status occurred (OR = 1.15; 95% CI: 1.02–1.31), whereas in the naMCI group this relationship was not observed. There is an association between cognitive dysfunction and impaired motor performance in older adults with MCI.